Denormalising smoking in the classroom: does it cause bullying?. Issue 3 (18th September 2009) - Hanewinkel, Reiner; Isensee, Barbara; Maruska, Karin; Sargent, James D; Morgenstern, Matthis
Abstract : Background: The Smokefree Class Competition, the largest school-based smoking prevention programme in Europe, aims to create a class climate that denormalises smoking. An analysis was carried out to assess whether it increases bullying or perception of isolation. Methods: A cluster randomised controlled trial was conducted, with two waves of assessment directly before the start and immediately after the end of the prevention programme. Some 3490 students were recruited from 84 secondary schools in Germany, of whom 3123 students (90%) provided data from both waves. Classes from the intervention group (IG) participated in the Smokefree Class Competition, committing themselves to stay smokefree for a period of 6 months, and self-monitoring their smoking status on a weekly basis. Classes that refrained from smoking were eligible for a prize draw. To test the hypotheses that participation in the competition might foster bullying, we measured students' self report of (1) being victimised, (2) engaging in bullying and (3) being isolated. Results: There was a strong association between daily smoking and higher odds of bullying others at baseline (adjusted proportional OR 4.66; 95% CI 3.38 to 6.43). No significant pre–post differences across treatment assignment groups were found on any bullying measure using generalised linear latent and mixed models. For being isolated, the trends suggested that the programme, if anything, fostered lower levels of isolation at follow-up, especially for those who perceived high levels of isolation at baseline. Conclusion: Participation in the intervention had no effect on bullying or perceptions of isolation. Trial Reg No: ISRCTN27091233 in Current Control Trial Register.